Observation of B 0 → ψ (2S)K S 0 π + π - and B s 0 → ψ (2S)K S 0 decays - Tumasyan, A; Adam, W; Andrejkovic, J W; Bergauer, T; Chatterjee, S; Damanakis, K; Dragicevic, M; Valle, A Escalante Del; Frühwirth, R; Jeitler, M; Krammer, N; Lechner, L; et al. (The European physical journal. C, Particles and fields, 2022)
Using a data sample of s = 13 TeV proton-proton collisions collected by the CMS experiment at the LHC in 2017 and 2018 with an integrated luminosity of 103 fb - 1 , the B s 0 → ψ ( 2S ) K S 0 and B 0 → ψ ( 2S ) K S 0 π + π - decays are observed with significances exceeding 5 standard deviations. The resulting branching fraction ratios, measured for the first time, correspond to B ( B s 0 → ψ ( 2S ) K S 0 ) / B ( B 0 → ψ ( 2S ) K S 0 ) = ( 3.33 ± 0.69 ( stat ) ± 0.11 ( syst ) ± 0.34 ( f s / f d ) ) × 10 - 2 and B ( B 0 → ψ ( 2S ) K S 0 π + π - ) / B ( B 0 → ψ ( 2S ) K S 0 ) = 0.480 ± 0.013 ( stat ) ± 0.032 ( syst ) , where the last uncertainty in the first ratio is related to the uncertainty in the ratio of production cross sections of B s 0 and B 0 mesons, f s / f d .